Relationships between strength, sprint, and jump performance in well-trained youth soccer players - Comfort, P.; Stewart, A.; Bloom, L.; Clarkson, B. (The Journal of Strength and Conditioning Research, 2014)
Research has demonstrated a clear relationship between absolute and relative strength and sprint and jump performance in adult athletes; however, this relationship in younger athletes has been less extensively studied. The aim of this study, therefore, was to determine the relationships between strength, sprint, and jump performances in well-trained youth soccer players. Thirty-four young male soccer players (17.2 ± 0.6 years; body mass, 72.62 ± 7.42 kg; height, 179.27 ± 6.58 cm) performed a predicted maximal squat test, 20-m sprints, squat jumps (SJs), and countermovement jumps (CMJs). Absolute strength showed the strongest correlations with 5-m sprint times (r = -0.596, p < 0.001, power = 0.99), SJ height (r = 0.762, p < 0.001, power = 1.00), and CMJ height (r = 0.760, p < 0.001, power = 1.00), whereas relative strength demonstrated the strongest correlation with 20-m sprint times (r = -0.672, p < 0.001, power = 0.99). The results of this study illustrate the importance of developing high levels of lower-body strength to enhance sprint and jump performance in youth soccer players, with stronger athletes demonstrating superior sprint and jump performances.